A Model To Implement Of Strategic Plans - Nader Mazloomi; Ali Motevalli (مطالعات مدیریت بهبود و تحول, 2012)
Strategic management contains three major stages, planning, implementation, and control, assessment. Implementation the strategies is the general stage of strategic management. setting up a strategy which never gone to be Implemented, is a waste. So the next step after setting the strategy is implementation, to transform long strategies to short activities and optimal targets. The implementation stage is the most difficult stages, since the ideas and strategic approach should transform to the practice. Many strategy plans just documented in organizations but there is no implementation, because manager dose not focuses to the implementation as well as setting the strategy. This paper emphases and focused to the specifications which can act as the variable to simplify implementation of strategies. In the other word the target of this study is to identify and determine suitable conditions in organizations to implement a strategy. In this paper two manufacturing companies (a public stock and a private stock) and a servicing company (private stock) is studied deeply and interviewed with more than 23 manager, advisor and, strategy planer across the companies. These companies had the documented strategy plan and implemented that strategy. Then by utilizing the fundamental Theory research methodology, the interviews texts were coded and various concepts and categories exported. These categories again approved by the interviewers and finally delivered a model base on the paradigm model framework. The constitutive factors of this model have shown how the strategic plans can implemented in a rational view. Actually this model has shown the transformation stage of strategy plan to the practice. In the other word the model determines the suitable conditions for implementation of the strategy. Using this model can fill the gap between setting a strategy and to put it in practice and make it implementable.